First Results of a Campaign of the Measurement of Polycyclic Aromatic Hydrocarbons in the Sediments of the Hooghly River, West Bengal, India - Michele Arienzo; Maria Toscanesi; Luciano Ferrara; Carlo Donadio; Priyanka Mondal; Jonathan Muthuswamy Ponniah; Gaetana Napolitano; Santosh Kumar Sarkar; Marco Trifuoggi (Journal of Marine Science and Engineering, 2024)
This study presents the first data on a 2018–2021 campaign to monitor polycyclic aromatic hydrocarbon levels, PAHs, in the final stretch of the Hooghly River in West Bengal, India. The range of sedimentary PAHs was 0–47,366 ng/g, higher than the ranges given by the literature for comparable study areas. The assay reveals an outstanding level of PAHs contamination in the fine sediments of the Hooghly River and Sundarban wetland, where the dominance of 4–6 ring PAHs was 83% of the total. The diagnostic ratios based on molecular ratios of PAHs show that the pollution comes mainly from the combustion of petroleum. The ratio of anthracene relative to anthracene plus phenanthrene, ANT/(ANT + PHE), was >0.30, which is higher than the reference discriminant ratio of >0.10, suggesting that PAHs were from the combustion source. In the meantime, fluoranthene over the sum of fluoranthene plus pyrene, FLT/(FLT + PYR), was >0.5 and indicated coal combustion, in agreement with the literature. The mean level of carcinogenic hydrocarbons was at 18% of the total measured PAH, with a peak of 91%, revealing significant potential risk for humans and ecosystems. The toxicity equivalence factors, TEF, of the individual PAHs and the total BaP equivalent toxicity, TEQ, were adopted as a comparison reference of sediment quality. At most sites, toxic effect ranges were classified as high and very high. The results of this research call for public authorities to remedy a situation of severe ecological risk.